Central and Regional Relations in Managing Gelora Bung Karno Area - Megandaru Widhi Kawuryan; Alma Arif (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
This study uses a qualitative paradigm with descriptive research type. Informants weredetermined by purposive sampling method with qualitative data analysis. The resultsshowed that the Management of Bung Karno Gelora Complex Area which has beenmanaged by the Managing Directors responsible to the Bung Karno ComplexManagement Agency (PKKGBK) still has some fundamental obstacles such asinstitutional aspects that are full of causing patron clients, aspects of work area whichare in line with the working area of DKI Jakarta Province, aspects of funding that cancome from local governments but regional governments cannot intervene in regionalmanagement policies, as well as overlapping spatial and regional governance aspects.The future management of the Bung Karno Gelora Complex Area can be done in 2(two) ways that are taken in stages. The first stage can be done by building institutionalcoordination between central and regional institutions whose financial managementcan be done cost sharing and revenue sharing. When a coordinating institution hasbeen formed, it can move forward with the establishment of functional decentralizedgovernment institutions by giving authority to stakeholders using GBK services aspracticed by several developed countries in the management of special areas.